Dampak Kualifikasi Auditor dan Penggunaan Teknologi Audit terhadap Efektivitas Proses Audit di Perusahaan Manufaktur di Indonesia - Judijanto, Loso (Sanskara Akuntansi dan Keuangan, 2024)
This study investigates the impact of auditor qualifications and the use of audit technology on the effectiveness of the audit process in manufacturing companies in Indonesia. Using a quantitative approach, data was collected from 70 auditors through structured questionnaires and analyzed using SPSS version 26. The findings show that auditor qualifications and the use of audit technology significantly contribute to the effectiveness of the audit process. Auditor qualifications, including certifications and experience, were found to positively influence the accuracy and reliability of audits. Additionally, audit technology enhances efficiency and reduces errors in the audit process. Regression analysis confirms that both variables have a positive and significant impact on audit effectiveness. These results highlight the importance of continuous professional development for auditors and the use of advanced technology in ensuring effective audits in the manufacturing sector.